Educação antirracista e material didático: Análises, perspectivas e possibilidades para a sala de aula - Souza, Angelio Santos de (2024)
Starting from the perspective that the textbook is an important instrument for the education and critical awareness of students today, we propose a reflection on the teaching of History and its approach through the textbook, as well as the influence of the BNCC in this process. The research was carried out based on the analysis of the FTD publisher's textbook collection for the eighth years and which are in accordance with the BNCC to discuss not only the approaches and contents but also the way they are worked in the researched textbook. Therefore, we focus on how the insertion of content focused on AfroBrazilian culture is worked on in textbooks in accordance with current legislation. In this way, we observed how the influence of educational legislation occurred in the creation of this textbook and its uses. Finally, considering the specificity of PROFHISTÓRIA, we seek to point out the pedagogical possibilities of anti-racist education in the classroom. In this sense, we propose the elaboration of a didactic sequence of the contents analyzed in the dissertation, the construction of a teaching material that can contribute to the teacher in the classroom in approaching the contents listed, provision of sources and theoretical discussions relevant to the content.